Electrochemical characterization of chromium deposition from trivalent solutions for decorative applications by EQCM and near-surface pH measurements. (20th April 2018) - Leimbach, Martin; Tschaar, Christoph; Schmidt, Udo; Bund, Andreas
Abstract: In chromium electroplating for decorative applications, trivalent chromium based electrolytes are recently used as alternatives for solutions of chromic acid. Since the use of hexavalent chromium is restricted in serval countries, the demand on chromium(III) electrolytes increases and there is a need for understanding the deposition kinetics in order to improve the performance of the plating process. Electrochemical quartz crystal microbalance (EQCM) was used to study the mass-charge balance of the cathodic processes in chromium(III)-sulfate based plating baths. Current efficiency and deposition rate were determined as a function of time, additive concentration and current density. The addition of benzoic sulfimide (BSI) facilitates the reduction to chromium metal, as an optimum current efficiency of 8.1% was observed at 2.5 A dm −2 . pH changes near the cathode surface during electroplating were evaluated in-situ by combining a pH electrode with a metal mesh and correlated with the results obtained by EQCM.